Is Child Abuse a Destiny Case Report - Biçer, Ümit; Çolak, Başar; Coşkun, Ayşen; Demirbaş, İlkgül; Kurtaş, Ömer; Gündoğmuş, Ümit Naci (The Bulletin of Legal Medicine, 2002)
In disclosure of 'abuse 'cases and these being taken to the court, medical reports do not reveal abuse cases due to the doctor's not having appropriate training his or her unwillingness to get involved in in family problems, and being unable to consider the fact that parents may harm the child. Two sisters examined, were subject to physical and sexual abuse. After the abuse case has been taken to the court, the youngest brother (8 months old) had to receive treatment because of a deep and extensive burn. And very soon after this, the 4 year-old sister together being with her mother, died in a minibus accident. A conference on child abuse was given to an audience with jurists being available by our faculty of forensic medicine. The conference was held virtually at a time just when the case was introduced. The attorney general, who met the family in inquiry, sued the father for public good although the sisters had given up their complaints. The topic was discussed with respect to education, physical sexual, abuse and negligence.Key words: Sexual abuse, physical abuse, negligence, incest, public education.
Keywords: sexual abuse; physical abuse; negligence; incest; public education